Calibrating VISSIM for the German Highway Capacity Manual. Issue 1 (January 2015) - Leyn, Ulrike; Vortisch, Peter
The German Highway Capacity Manual provides analytical methods to assess the level of service of freeway segments. If these segments do not comply with design guidelines, microscopic traffic simulation is often used to perform quality analysis. To provide guidance and support for these simulation studies, a research project was performed to develop a methodology for the assessment of levels of service and to find standard parameter sets calibrated for the simulation of German freeways. In this paper, the results of the microscopic simulation tool VISSIM, including a short description of the characteristics of German freeways, model settings, and specific parameter sets for several types of freeway segments, are presented.